2021
DOI: 10.4236/ajibm.2021.115026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Access to Credit for Vegetable Farmers in the Gulf Prefecture of Togo

Abstract: This paper addresses the issue of access to credit for market gardeners in the Gulf prefecture of southern Togo. Beyond structural constraints, individual socioeconomic characteristics of market gardeners are factors that play a role in access to credit. The binomial logit regression model was used as an analytical tool. From the National Agricultural Census (NAC, 2011) database, 452 market gardeners were randomly selected. The results showed that gender, membership in a financial solidarity group, sown area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…Consequently, they may charge higher interest rates to mitigate perceived risks, making it more challenging for farmers to access credit. This agrees with Julien, Kossi, and Aklésso (2021). 89.6% of the respondents feel that lack collateral security is another major problem associated with accessing to credit facilities.…”
Section: Major Problems Associated With Accessing Credit Facilitiessupporting
confidence: 71%
“…Consequently, they may charge higher interest rates to mitigate perceived risks, making it more challenging for farmers to access credit. This agrees with Julien, Kossi, and Aklésso (2021). 89.6% of the respondents feel that lack collateral security is another major problem associated with accessing to credit facilities.…”
Section: Major Problems Associated With Accessing Credit Facilitiessupporting
confidence: 71%
“…To investigate the determinants of credit access, many studies (Ankrah Twumasi et al, 2021;Baiyegunhi, 2008;Phan, 2012;Sossou et al, 2017) have used producers' socio-demographic characteristics, household characteristics, farm variables, financial structure variables as well as those of their products and other factors. Phan, (2012) and Julien et al, (2021) used individual characteristics (age, gender, education level, main occupation) and household characteristics (size, agricultural land size, land ownership) to determine factors that influence microcredit access. In addition to the above factors, Baiyegunhi, (2008) also includes the variables "credit awareness" and the "assets" and other factors as those likely to determine credit access in the Eastern Cape Province, South Africa.…”
Section: Definition Of Model Variablesmentioning
confidence: 99%
“…The results indicated that some of the factors that influenced access to credit included saving of money in commercial banks, owning a size of land that is less than 1 ha (0-0.1 ha) and knowledge of the repayment terms of the loan. Julien et al 12 assessed the factors influencing access to credit for vegetable farmers in the Gulf Prefecture of Togo using a Logit regression model. The findings indicated that beyond structural constraints, the socio-economic attributes of the market gardeners played significant roles in accessing credit.…”
Section: Introductionmentioning
confidence: 99%